Discursive strategies of resistance on Weibo: A case study of the 2015 Tianjin explosions in China. (December 2018) - Wu, Xiaoping
Abstract: The internet and social media are increasingly seen as one of the major channels for public participation and through which anxiety and discontent about social and political issues are voiced and dealt with in non-democratic countries like China. Weibo, as a platform of this type, has been attracting growing attention in the fields of political communication and media studies in recent years. This study takes a discourse approach to explore resistance on Weibo by drawing upon a case study of the 2015 Tianjin explosions. Based on a discourse analysis of 1322 microblogs immediately following the explosions, this study unravels the details and dynamics of how Weibo users challenge the official discourse and offer an alternative discourse of the disaster online. It identifies three discursive strategies of resistance in Weibo: (a) resisting by quoting cross-platform witness accounts; (b) resisting by creating rumors; (c) resisting by ridiculing the official discourse through satire. These strategies of resistance exemplify how Chinese netizens actively use social media platforms to express sociopolitical arguments in non-democratic contexts, and in turn, reshape the power relations between the state and the public.